Thermodynamic Cycle Evaluation of Rhombic Drive Beta-configuration Stirling Engine - Mohd Farid, Zainudin; R. A., Bakar; Gan, Leong Ming; Billy, Anak Sup (Elsevier Ltd, 2015)
The progressive developments and improvements of Stirling engines show significant effort in reducing the global emission level. The ability to use multiple kinds of heat sources with low emission level make it as a promising alternative solution in providing a healthier environment for natural population. For the present work, the thermodynamic cycle evaluation is conducted to a numerical model of proposed design of single-cylinder rhombic drive beta-configuration Stirling engine. The evaluation is carried out based on Schmidt ideal adiabatic model presented by Berchowitz and Urieli. The evaluation is based on three working space volumes of proposed beta-configuration engine. The prediction of reciprocating displacement, engine volumetric displacement, working fluid cycle pressure, working fluid instantaneous mass, cyclic energy flow and cyclic temperature are carried out and discussed. The proposed design's performance can be enhanced by maximizing the operating temperature difference between heat and sink source. Besides, the pressurization method could increase the thermal energy absorption and rejection thus enhancing the engine performance.